Downtime Analysis of Ultrasound Maintenance Using Failure Mode and Effects Analysis (FMEA) as a Risk‑Management Strategy in Radiology Services at YARSI Hospital, 2025 - Muhammad Umar Aziz; Melanie Husna; Sri Wuryanti; Dicky Budiman; Hendrana Tjahjadi (International Journal of Advanced Health Science and Technology, 2025)
The radiology department of YARSI Hospital experienced considerable ultrasonografi equipment downtime in 2025, disrupting diagnostic continuity and decreasing patient satisfaction. This study aimed to identify the principal causes of USG downtime and to formulate risk‑mitigation strategies using Failure Mode and Effect Analysis (FMEA). A descriptive, case‑study design was adopted; data were gathered over a twelve‑month period through field observations, semi‑structured interviews with ten technicians and biomedical engineers, and review of maintenance logs containing 312 recorded incidents. The collected information was processed within the FMEA framework identifying failure modes, assigning severity, occurrence, and detection scores, and calculating the Risk Priority Number (RPN) for each mode. The analysis revealed three critical failure modes: (1) Preventive maintenance  of the spare‑parts availability, (2) technician readiness, and (3) inter‑departmental communication. The spare‑parts‑availability mode obtained the highest RPN (RPN = 100), indicating it as the primary risk factor. Guided by the RPN ranking, a bundle of preventive‑maintenance actions was prioritized and scheduled before any equipment failure occurs: (i) proactive inventory management of critical spare parts, (ii) continuous competency‑building programs and certification for technicians, and (iii) implementation of a structured internal communication platform for coordinated repair activities. Modeling the projected impact of these interventions suggests a potential reduction of USG downtime by up to 40 % within the first six months, thereby improving equipment availability and overall radiology service quality. The study concludes that FMEA is an effective risk‑management tool for pinpointing critical failure factors and directing preventive‑maintenance measures, ultimately strengthening the reliability and safety of ultrasound services at YARSI Hospital.